Assessment of tuberculin reactivity of BCG-vaccinated infants in Zaria, Nigeria - Gambo, Mahmud; Lawan, Umar; Ahmad, Hafsat; Ogala, William (Nigerian Journal of Basic and Clinical Sciences, 2026)
Introduction: Tuberculosis (TB) is a serious public health problem associated with high morbidity and mortality. BCG vaccination as part of TB prevention strategy is faced with many challenges. The study sought to determine post BCG vaccination scarring and tuberculin reactivity, which may serve as useful indicators of routine BCG vaccination in infants. Materials and Methods: The study was descriptive cross-sectional. Infants were selected and physically examined for presence and size of BCG scar. Mantoux test was performed. Data were analyzed using statistical package for the social sciences software (SPSS version 16.0). Chi-square and Fisher’s exact tests were used for association between categorical variables while Pearson’s correlation co-efficient was used for the correlation between BCG scar size and Mantoux reaction.P≤ 0.05 was considered significant. Results: The male:female ratio of the subjects was 1.6:1.0 with a mean birth weight of 3.2 ± 0.4kg. Mean age at Mantoux test was 19.0 ± 3.0 weeks and the prevalence of BCG scar was 81.5% with a mean scar size of 5.3 ± 3.2mm. Mantoux test was positive in 202 (56.7%), negative in 133 (37.4%), and indeterminate in 21 (5.9%) infants. The Mantoux reaction was significantly associated with the age interval between BCG administration and time of Mantoux test (χ2= 54.17, P< 0.05), the infants’ gender (χ2= 31.23, P< 0.05) and their nutritional status (χ2= 22.60, P< 0.05). The reaction was not significantly associated with the social class of the infants’ parents. Conclusion: The study demonstrated high prevalence of BCG scar and high Tuberculin skin test reaction. Regular evaluation of BCG vaccination is recommended using TST and scar observation as adjuncts to strengthen BCG vaccination processes for effective tuberculosis prevention.